Heritability and interindividual variability of regional structure-function coupling - Zijin Gu (Nature Portfolio, 2021)
The relationship between the human structural and functional connectome is still not well established. Here the authors show the interindividual variability that exists in regional coupling of structural and functional connectivity across the brain, and that this is heritable.